Women and Leadership in Banking Sector: Opportunities and Challenges Within Malay Cultural Values - Tessa Shasrini; Al Sukri; Yudi Daherman (Communicare : Journal of Communication Studies, 2026)
The increasing presence of women in banking leadership reflects progress in workplace gender inclusion; however, structural and cultural barriers remain, particularly in societies with strong traditional values such as Malay culture. This study examines the opportunities and challenges faced by women leaders in the banking sector and the influence of Malay cultural values on their leadership experiences. This study employed a qualitative case study approach. Data were collected through in-depth interviews, observation, and documentation involving five female leaders from banking institutions in Pekanbaru. The findings show that women gain leadership opportunities through educational qualifications, professional competence, work performance, and merit-based organizational support. Participants demonstrated participative and transformational leadership characterized by effective communication, empathy, and collaboration. However, they continued to face role conflict, gender stereotypes, and cultural expectations emphasizing women’s domestic responsibilities. Malay cultural values shape women’s leadership in complex ways by promoting harmony, responsibility, and interpersonal sensitivity while also reinforcing traditional gender norms that may constrain career advancement. These findings highlight the interaction between organizational meritocracy, leadership competence, and sociocultural expectations in shaping women’s leadership experiences in the banking sector.